PELAKSANAAN FUNGSI KELOMPOK KERJA KEPALA SEKOLAH DASAR NEGERI KECAMATAN KOTO TANGAH KOTA PADANG - Reni Ayu Fitra (Jurnal Bahana Manajemen Pendidikan, 2013)
This research is motivated by the implementation of the chief functions of the Working Group Elementary School District Koto Tangah Padang. The purpose of this study was to obtain information about the implementation of the Principal Working Group functions as a container to solve the problems faced by teachers, school management forum for oversight, the agency that gave birth to school leadership tips, and a forum to improve the quality of education. This is a descriptive study. Researchers to test the validity of the questionnaire to test methods using the formula rank correlation (Spearman method). Based on the results of research in general has a score of 4.16. This means that the implementation of the main functions of the Working Group of State Koto Tangah Padang district with a population of 57 elementary school principal has been going well. Keyword: Implementation Working Group Principal function